ON THE USE OF BILINGUAL TECHNOLOGIES IN THE PROCESS OF LEARNING ENGLISH THE LANGUAGE IN HIGH SCHOOL - Grigorieva, K.S.; Yakhina, R.R. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Informatizat͡s︡ii͡a︡ obrazovanii͡a, 2017)
At present, the application of information and communication technologies (ICT) in learning English in high school proved its effectiveness. The article presents the differentiation of the concepts of CLIL (Content and Language Integrated Learning) and EMI (English as a Medium of Instruction) and given the definitions of these terms; the choice of educational technologies CLIL. Analyzed psychological and psycholinguistic problems in the learning process of students and possible ways of their solution. The article discusses the possibility of using Internet resources as a means of learning within CLIL.